Earthworm Protease - Rong Pan; Zi-Jian Zhang; Rong-Qiao He (Applied and Environmental Soil Science)
The alimentary tract of earthworm secretes a group of proteases with a relative wide substrate specificity. In 1983, six isozymes were isolated from earthworm with fibrinolytic activities and called fibriniolytic enzymes. So far, more isozymes have been found from different earthworm species such as Lumbricus rubellus and Eisenia fetida. For convenience, the proteases are named on the basis of the earthworm species and the protein function, for instance, Eisenia fetida protease (EfP). The proteases have the abilities not only to hydrolyze fibrin and other protein, but also activate proenzymes such as plasminogen and prothrombin. In the light of recent studies, eight of the EfPs contain oligosaccharides chains which are thought to support the enzyme structure. Interestingly, EfP-II has a broader substrate specificity presenting alkaline trypsin, chymotrypsin and elastase activities, but EfP-III-1 has a stricter specificity. The protein crystal structures show the characteristics in their specificities. Earthworm proteases have been applied in several areas such as clinical treatment of clotting diseases, anti-tumor study, environmental protection and nutritional production. The current clinical utilizations and some potential new applications of the earthworm protease will be discussed in this paper.